3(4x+5)-5(7x-7)=2(6x+1)

Simple and best practice solution for 3(4x+5)-5(7x-7)=2(6x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+5)-5(7x-7)=2(6x+1) equation:


Simplifying
3(4x + 5) + -5(7x + -7) = 2(6x + 1)

Reorder the terms:
3(5 + 4x) + -5(7x + -7) = 2(6x + 1)
(5 * 3 + 4x * 3) + -5(7x + -7) = 2(6x + 1)
(15 + 12x) + -5(7x + -7) = 2(6x + 1)

Reorder the terms:
15 + 12x + -5(-7 + 7x) = 2(6x + 1)
15 + 12x + (-7 * -5 + 7x * -5) = 2(6x + 1)
15 + 12x + (35 + -35x) = 2(6x + 1)

Reorder the terms:
15 + 35 + 12x + -35x = 2(6x + 1)

Combine like terms: 15 + 35 = 50
50 + 12x + -35x = 2(6x + 1)

Combine like terms: 12x + -35x = -23x
50 + -23x = 2(6x + 1)

Reorder the terms:
50 + -23x = 2(1 + 6x)
50 + -23x = (1 * 2 + 6x * 2)
50 + -23x = (2 + 12x)

Solving
50 + -23x = 2 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
50 + -23x + -12x = 2 + 12x + -12x

Combine like terms: -23x + -12x = -35x
50 + -35x = 2 + 12x + -12x

Combine like terms: 12x + -12x = 0
50 + -35x = 2 + 0
50 + -35x = 2

Add '-50' to each side of the equation.
50 + -50 + -35x = 2 + -50

Combine like terms: 50 + -50 = 0
0 + -35x = 2 + -50
-35x = 2 + -50

Combine like terms: 2 + -50 = -48
-35x = -48

Divide each side by '-35'.
x = 1.371428571

Simplifying
x = 1.371428571

See similar equations:

| 0=x^2-9x-8 | | -(x+11)=2(2x-6) | | 5*(1/3)-(-2/3)X | | 2(6x-1)=120 | | -30=-14+v | | 4x=4(0+2x) | | 6x+68=9x-7 | | 2x+20+3x+8=180 | | -3=x-15 | | 9sin^2x+2=3 | | 2=2n | | 1x-20=10 | | b-5=-24 | | 5x+85=53 | | (36x)/(-8x) | | 2x+1=6x+(-23) | | 3k=-51 | | 3n+4=7n+4 | | 2+25x=20x+15 | | 3.4x=2.7 | | 5t+6=-24-t | | 36x/-8x | | b/3--17=20 | | y=-0.02x^2+1.6x | | 9x+9=8x+5 | | -2x-8x= | | 3(x-5)=2x+30 | | 2.7x-0.05x+0.75x=3.4x | | v/3-3=1 | | 36x=-8x | | 25b^4-211b^2+3024=0 | | 3(n-2)=3(2n+4) |

Equations solver categories